KAJIAN AKUNTABILITAS KEUANGAN DAN TRANSPARANSI DALAM MENILAI KINERJA PEMERINTAHAN DESA - Aziz, Nur Jannah Abdi; Winda Ayu; Tiara (Perwira Journal of Economics & Business, 2024)
This study aims to explore the effect of financial accountability and transparency on village government performance in managing village finances. The research method used is quantitative method using multiple regression analysis. Data were collected through the distribution of questionnaires, documentation techniques, and  interviews. The results showed a significant relationship between financial accountability, transparency, and village government performance. The supporting evidence found in this study states that village governments that have a high level of financial accountability and a good level of transparency tend to have better performance in managing village finances. Next research can be enriched by involving qualitative analysis and involving a wider sample of respondents.